ANTREAN KENDARAAN DI GERBANG TOL CIBUBUR UTAMA - Lis Lesmini; Dwika Ahadiputra; Hendro Kuntohadi (Institut Transportasi dan Logistik Trisakti, 2017)
The purpose of this research is to find out and analyze the transport waiting line / vehicle queue at toll gate of Cibubur Utama. The analysis method used was Multiple Server Queue System - single stage. Based on the calculation and analysis obtained service time at the main cibubur toll gate is 9.064 seconds / vehicle. At the average level of business (r) reached 70 %. Peak Hours condition reached 170 % means that it is more than Over Utilized. Low Hours condition reached 39 %. The average number of vehicles queuing up (Lq) on average condition is 0.0241 vehicles. Peak Hours condition is 158 vehicles. Low Hours condition is 0.00003 vehicles. Average time vehicle queue (Wq) on average condition is for 0.028 seconds. Peak Hours condition is for 77 seconds. Low Hours condition is 0.00007 seconds. The average number of vehicles in the system (L) on the average condition is 7 vehicles. The condition of Peak Hours is 177 vehicles. Low Hours condition is as many as 4 vehicles. Average vehicle time is in system (W) at average condition for 9.092 seconds, Peak Hours condition for 86 seconds, and Low Hours condition for 9.064 seconds. In Peak Hours condition, the capacity of the main cibubur toll gate is not able to accommodate the number of vehicle arrival rates.